Histological aspects of digestive tract Tropidurus peruvianus peruvianus (Lesson) - Paz-Castillo B., Julio (1974)
A histological study of the digestive tract of the Tropidurus peruvianus peruvianus (Lesson) has been performed. With the staining techniques applied here the best results were guaranteed with the Horris hematoxiline-eosin method and Von-Giesson's, and noting the sistematic difference in comparing it with another vertebrates.